-5v(v-1)(v+3)=0

Simple and best practice solution for -5v(v-1)(v+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5v(v-1)(v+3)=0 equation:


Simplifying
-5v(v + -1)(v + 3) = 0

Reorder the terms:
-5v(-1 + v)(v + 3) = 0

Reorder the terms:
-5v(-1 + v)(3 + v) = 0

Multiply (-1 + v) * (3 + v)
-5v(-1(3 + v) + v(3 + v)) = 0
-5v((3 * -1 + v * -1) + v(3 + v)) = 0
-5v((-3 + -1v) + v(3 + v)) = 0
-5v(-3 + -1v + (3 * v + v * v)) = 0
-5v(-3 + -1v + (3v + v2)) = 0

Combine like terms: -1v + 3v = 2v
-5v(-3 + 2v + v2) = 0
(-3 * -5v + 2v * -5v + v2 * -5v) = 0
(15v + -10v2 + -5v3) = 0

Solving
15v + -10v2 + -5v3 = 0

Solving for variable 'v'.

Factor out the Greatest Common Factor (GCF), '5v'.
5v(3 + -2v + -1v2) = 0

Factor a trinomial.
5v((1 + -1v)(3 + v)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'v' equal to zero and attempt to solve: Simplifying v = 0 Solving v = 0 Move all terms containing v to the left, all other terms to the right. Simplifying v = 0

Subproblem 2

Set the factor '(1 + -1v)' equal to zero and attempt to solve: Simplifying 1 + -1v = 0 Solving 1 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1v = 0 + -1 -1v = 0 + -1 Combine like terms: 0 + -1 = -1 -1v = -1 Divide each side by '-1'. v = 1 Simplifying v = 1

Subproblem 3

Set the factor '(3 + v)' equal to zero and attempt to solve: Simplifying 3 + v = 0 Solving 3 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + v = 0 + -3 v = 0 + -3 Combine like terms: 0 + -3 = -3 v = -3 Simplifying v = -3

Solution

v = {0, 1, -3}

See similar equations:

| 7×4/21 | | log(8)(x+6)+log(8)(x+4)=1 | | 7x^3+60x^2-27x=0 | | 27y+7= | | 7a^3-17a^2+6a=0 | | 8x=-12+5x | | t-34=15 | | p=y^2-12y | | 7x+16=5x | | f(x+4)=3x-9x | | 16a^2b-32a^2b^3+24a^3b= | | 7x^3+66x^2+27x=0 | | 4y-43=9(y-7) | | 5x-(x-5)=17 | | d+16=19.69 | | 180=x-5 | | 14x-2(6x+7)=-4 | | mx/r=4r | | 10-2x=-3(x+5) | | 2(x-4)-6x=12 | | 3-6m+10m+8=8m-7 | | 17x-5(10+5x)=2(-6x+7) | | 57x=9 | | 12x-(x-39)=11+4x | | 3(X-6)=2x-9 | | 11x-4y=-32 | | 5x^2+48z+28=0 | | 9x-7=3x+2 | | -5x+12=-3x-8 | | 255=-5(7x-2) | | -(x+1)=3(x+5) | | 4x+60+9x-40=180 |

Equations solver categories